LITERACY BASED SHARING KNOWLEDGE ON THE COMMUNITY - Andi Asari; Dwi Saksomo; Amalia Nurma Dewi; Dwi Novita Ernaningsih (Jurusan Sastra Indonesia, 2018)
This study is a community-based information literacy studies on DPD PERTUNIcommunity Malang. The purpose of this study is to describe the role of communitiesin developing information literacy PERTUNI members, describing the strategy andthe characteristics as contained in the Community Pertuni. The method used is aqualitative method with a case study approach. Through case studies of the results ofthis study indicate that information literacy using a social approach to take advantageof community ties, a significant role in information literacy community members.Recognized members of the community that they have a higher information literacywhile joining the community.